Knowledge, readiness and barriers factors to support the single-use plastic reduction programme among Kelantan street food hawkers using a new Malay version questionnaire - Abdullah, Nur Baizura Aini (2020)
Excessive usage of single-use plastic containers has imposed a serious environmental pollutions and health problems to human. Food hawkers had been contributing to this problem from high demand of ready-to-eat food and this need to be controlled. There is a need to assess the knowledge, readiness and barriers to support plastic reduction programme among street food hawkers. Objectives: This study involved the development and validation of a new questionnaire to assess knowledge, readiness and barriers of food hawkers to support single-use plastic reduction programme in Kelantan. This was a 2-phase study with Phase 1 involved the development and validation of a questionnaire done from December 2019 till March 2020, while Phase 2 involved the assessment of knowledge, readiness and barriers, their associated factors, and relationships between all these domains which was done from March 2020 till April 2021. Methodology: In Phase 1 study, the questionnaire was developed after thorough literature review and experts’ opinions from experts and hawkers’ representatives. Response process was done via cognitive debriefing and pretesting process. Item Response Theory (IRT), exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were done in psychometric evaluation of questionnaire. Internal consistency of all the items was also conducted. A total of 660 food hawkers fromKota Bharu district involved in the validation study recruited through purposive sampling. For Phase 2 study, a cross-sectional study was conducted involving 440 food hawkers from five districts in Kelantan. Proportionate sampling was done to get the sample size for each night market food hawkers. Level of knowledge, readiness and barriers, their associated factors were measured using descriptive statistics and multiple logistic regression. While Pearson correlation was used to find the relationship, strength and directions of these three domains. Results: The final version of SFH-RS tool consisted of 46 items (22 items on knowledge, 15 items on readiness and 9 items from barriers). 2-PL IRT analyses indicated good psychometric properties of items for discrimination index between 0.8- 2.5, and difficulty index between -3 to +3 was 86.7%. The marginal reliability value was 0.77. In EFA analysis for readiness and barriers domains, all four factors showed acceptable reliability with Cronbach alpha of more than 0.7. All items loaded with factor loading of > 0.4 and item communality of more than 0.25 and factor correlations were < 0.85 between all the factors. In CFA analysis, the final model consists of 24- items under 4 factors. This newly developed tool demonstrated acceptable factor loading with >0.5, Tucker-Lewis Index (TLI) = 0.906; Comparative Fit Index (CFI) = 0.916; and Root Mean Square Error of Approximation (RMSEA) = 0.056 with composite reliability of Rykov’s Rho value between 0.757 to 0. 887. Majority (71.8%) of the respondents had good level of knowledge score, ready (60%) to support plastic reduction program and consider barriers (73%) had low influence on them. Age (aOR=0.952; 95% CI: 0.93,0.97; p-value <0.001), readiness to change (aOR=3.271; 95% CI:2.046,5.230, p-value<0.001), and significant barriers (aOR=3.577; 95% CI:2.204,5.805, p-value<0.001), were found to be associated withknowledge level. Meanwhile, male food hawkers (aOR=1.706, 95% CI: 1.124, 2.590, p-value = 0.012), information source from social media (aOR=2.914, 95% CI: 1.852, 4.584, p-value <0.001) and official source of information (aOR=2.269, 95% CI: 1.343 3.835, p-value = 0.002) has been associated with readiness to support single-use plastic reduction program. It was found that there was a significant and direct moderate correlation between knowledge score and readiness score (r = 0.492, p-value < 0.001). Besides that, barrier’s score has a strong indirect correlation with knowledge score (r = -0.503), p-value < 0.001) and barriers and readiness score have a significant negative moderate correlation (r = - 0.479, p-value < 0.001). Conclusion: The SFH-RS is a reliable and valid tool used to assess knowledge and readiness among food hawkers to support single-use plastic reduction programme. Overall results in Phase 2 study showed good knowledge and readiness level, with majority of food hawkers did not consider barriers as significant in changing their action in supporting this programme. It also could identify significant factors to help in future or activities in plastic reduction program.